Trilogy Development of Proopiomelanocortin Neurons From Embryonic to Adult Stages in the Mice Retina - Zhang, Xuhong; Wang, Xiaoyu; Wang, Senjie; Peng, Wei; Ullah, Rahim; Fu, Junfen; Zhou, Yudong; Shen, Ye (Frontiers in Cell and Developmental Biology, 2021)
Proopiomelanocortin-positive amacrine cells (POMC ACs) were first discovered in adult mouse retinas in 2010; however, the development of POMC-ACs has not been studied. We bred POMC-EGFP mice to label POMC-positive cells and investigated the development of POMC neurons from embryonic to adult stages. We found that POMC neuron development is mainly divided into three stages: the embryonic stage, the closed-eye stage, and the open-eye stage. Each stage has unique characteristics. In the embryonic stage, POMC neurons appeared in the retina at about E13. There was a cell number developmental peak at E15, followed by a steep decline at E16. POMC neurons showed a large soma and increased spine numbers at the closed-eye stage, and two dendritic sublaminas formed in the inner plexiform layer (IPL). The appearance and increased soma size and dendrite numbers did not occur continuously in space. We found that the soma number was asymmetric between the superior and inferior retinas according to the developmental topographic map. Density peaked in the superior retina, which existed persistently in the retinal ganglion cell layer (GCL), but disappeared from the inner nuclear layer (INL) at about P6. At the same time, the soma distribution in the INL was the most regular. At the open-eye stage, the development of POMC neurons was nearly stable only with only an increase in the IPL width, which increased the soma–dendrite distance.